Structural Interpretation of the Viscous Flow and Relaxation Kinetics in the As-Se and Ge-Se Chalcogenide Systems - Honcová, Pavla; Košťál, Petr; Včeláková, Michaela; Svoboda, Roman; Sádovská, Galina; Barták, Jaroslav; Málek, Jiří (Elsevier Science BV, 2024)
This study investigates the behaviour of As20Se80 and Ge25Se75 chalcogenide glasses near the glass transition temperature using differential scanning calorimetry (DSC) and thermomechanical analysis (TMA), addressing a gap in the literature for these compositions. Precise TMA measurements of viscosity in the range of 10E6 - 10E13 Pa.s clarified existing data and improved the quality of fits describing the temperature-dependent viscosity for both compositions. The DSC method enabled a comprehensive analysis of structural relaxation behaviours, which were described using the Tool-Narayanaswamy-Moynihan (TNM) model with the determination of its four parameters. The study discusses the viscosity and structural relaxation behaviours of both glass-formers in relation to their structure, referencing previous results for other binary chalcogenide glasses in the As-Se and GeSe systems. The findings indicate significant changes in viscosity and activation energy of structural relaxation with the addition of As or Ge, while the non-linearity and non-exponentiality parameters remain largely unaffected.
Strukturní interpretace viskózního toku a relaxační kinetiky v chalkogenidových systémech As-Se a Ge-Se
Keywords: Viscosity; Structural relaxation; Chalcogenides; TNM model; Viskozita; Strukturní relaxace; Chalkogenidy; TNM model